Declining high-impact clinical publication rate: A potential contributor to health disparities among persons with developmental and intellectual disabilities - Priyanka R. Dharampuriya; Neha Singh; Susan L. Abend (Journal of Family Medicine and Primary Care)
Background: Persons with intellectual and developmental disabilities (IDD) suffer from stark, well-documented health and healthcare disparities, despite data indicating that the majority see a healthcare provider at least annually. Multiple surveys have indicated that over 90% of physicians feel they have inadequate knowledge and skill in caring for those with IDD. This has been recognized as a key barrier to health equity. Objective: To evaluate the content of high-impact clinical literature for a potential cause of clinician knowledge deficits. Methods: We performed a bibliometric analysis of publications within major, high-impact general, and specialty clinical journals from 1946 to 2020 to determine the relative frequency of publications regarding IDD and publication rate. Results: We observed a significant decline in articles regarding IDD over the past 20 years within high-impact general medical journals, and a significant decline over the past 15 years within high-impact, specialty society-published journals of Psychiatry, Psychology, and Neurology. Furthermore, we observed that high-impact general medical journals devoted a significantly smaller proportion of publication space to articles regarding IDD than they did for conditions with similar prevalence such as HIV/AIDS, breast cancer, and drug abuse. Conclusion: The declining rate and low frequency of clinical publications regarding IDD within the major, respected clinical literature may be contributing to physicians’ ability to source evidence-based information, thereby impacting perceptions of skill and knowledge deficits, and therefore may be contributing to healthcare disparities in this population. Well-designed clinical studies that engage persons with IDD may lead to an evidence base within the clinical literature that will improve physician confidence and care quality.